Performance comparison of AODV, DSDV and EE-DSDV routing protocol algorithm for wireless sensor network - Norhizat, Mohd Taufiq; Ishak, Zulkifli; Sauti, Mohd Suhaimi; Jamaludin, Md Zaini (2009)
This paper describes a preliminary study on wireless sensor network (WSN) routing protocol algorithm with focus on energy saving strategy.Efficient energy saving and consumption will ensure the lifespan of the battery are prolonged and the delay of transmitting data will be within the acceptable range of 300 meter by 300 meter network size.The routing protocol Ad-hoc On Demand Distance Vector (AODV), Destination Sequence Distance Vector (DSDV) and Energy Efficient Destination Sequence Distance Vector (EE-DSDV) were used in the study to compare the performance of the network in terms of maximum delay, throughput receive as well as the remaining energy in the network.